Pergeseran dan Pemertahanan Bahasa Daerah Pengrajin Kayu di Kabupaten Tegal - Amalia, Ayu Rizqi; Muhajir, Muhajir; Ripai, Ahmad (Jurnal Bahasa dan Sastra, 2024)
This research examines the maintenance and shift of Javanese and other regional languages among wood craftsmen in Tegal Regency, Indonesia. Regional languages are integral to cultural identity, and their retention or shift reflects broader social and cultural dynamics. Using a qualitative case study approach, data was collected through observation, interviews, questionnaires, and documentation. The study employs thematic analysis to provide an in-depth understanding of language use patterns. Findings reveal a linguistic dualism in the community. While Indonesian dominates formal situations, reflecting adaptation to broader communication needs, Javanese and other regional languages prevail in daily interactions, indicating the continuity of local cultural traditions. This language shift and maintenance are influenced by social context, education, and work environment factors. The study contributes to our understanding of language ecology in multilingual Indonesian contexts, drawing on Fishman's domain analysis. It highlights how communities navigate between national and regional languages, adapting to different communication needs while preserving cultural identity. These findings have implications for language policy and cultural preservation efforts in Indonesia, particularly in balancing national unity with linguistic diversity.